(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2017)
It is very important to motivate employees in the process of their work to achieve high productivity. For better understanding of the meaning of motivation, the article investigates the essence and the meaning of human labor. It is proved that the most valuable is the work, where the employee feels their own necessity and usefulness. This opinion is more closely adhered to by employees of the mature age. Those kinds of work where organization of work is better, teamwork is preferable, working conditions arefavorable become more attractive to youngemployees. Middle ageworkers are interested toincrease their vocational qualifications, whereas achieving a certain age limit, this pattern begins to decline. The important factors in the staff motivation are the subjective factors of the choice of profession and the level of skills, determined by the level of prestige of work. Certain groups of factors influence the quality of the work and jobsatisfaction. However, the article notes that there are more factors that decrease the level of readiness to work. The reasons to demotivate the staff are as following: unfair payment, poor working conditions, lack of organizational clarity, inappropriate leadership style, badly formed corporate culture, lack of professional growth, lack of training opportunities, lack of qualified professionals and managers who are able to evaluate and decide whether the candidate is skilled enough to suit the available vacancy, inability to provide high-skilled workers with their further growth, recruitment of employees who are not interested in the job, discrepancy between expectations of employees and the enterprise, the inability of the employee to respond quickly and make the right decisions in a non-standard situation, the absence of conditions under which the employee’s motives would contribute to his effective professional activities, etc. Understanding of the reasons for reducing of motivation is the key to successful personnel management.